A Kajian Aktivitas Ekonomi Dan Rekreasi Terhadap Fungsi Buffer Zone Di Kecamatan Meuraxa, Banda Aceh: Study Economic and Recreational Activities on Buffer Zone Function in Meuraxa District, Banda Aceh - Nadya Bestnissa; Sausan Maulida, Sitti; Westy Putri, Alissia (Jurnal Engineering, 2025)
Meuraxa District is highly vulnerable to tsunamis. Although designated as a disaster-prone area, it is also designated as a tourism destination in Banda Aceh City. Furthermore, Meuraxa District has been designated as a coastal green open space (RTH) as a protective belt or buffer zone that absorbs the energy of tsunami waves from the coast. Green Open Space (RTH) plays a crucial role in urban life and the environment, including its economic function. This study aims to examine the patterns of economic and recreational activities within the RTH, which serves as a buffer zone in Meuraxa District, and the impacts of these activities. Observations indicate that economic and recreational activities can coexist, with each activity operating without interfering with the other.